(untitled) (Research, Society and Development, 2022)
The Brazilian electricity sector is predominantly supplied by clean and intermittent sources of electricity. Intermittency and complementation must be done by other energy sources to further add to the supply of clean energy for Brazil. Natural gas can be one of these sources since it exists in abundance and pollutes less than other fossil fuels such as coal and diesel oil. However, the integration between the electric sector and natural gas must be planned for the development of both and for the benefit of the consumer. Law 14.182/21, authorizes the privatization of Eletrobras (Brazilian Energy Company). The law makes provision for the contracting of 8 GW of thermal energy generation, moved by natural gas, by means of capacity auctions. It further defines in which regions of Brazil that the thermal plants should be installed. In this sense the objective of this article is to make some reflections on the provisions of Law 14.182/21 with respect to the Brazilian electricity sector and the increased participation of natural gas in the national electricity matrix.